Pemanfaatan Resi Gudang Sebagai Opsi Optimalisasi Supply Chain Sebagai Alternatif Solusi Harga Panen Anjlok Pada Kelompok Tani - Handy Nur Cahya (JRB-Jurnal Riset Bisnis, 2019)
TSince long ago this agricultural country, Indonesia has never been separated from rice farming. However, the welfare of farmers has not been fully good. The harvest season that should bring joy and profit, not always absolute about the full benefits. Harvest season are often accompanied by problems such as drop of selling price due to abundant supply. The purpose of this study is to diclose that farmer groups can optimize the supply chain flow to overcome the drop of selling price. This research was conducted in descriptive research, by conducting direct observations on Tirta Jaya farmer groups in Demak, then mapping the existing supply chain flow, and finally finding optimization solutions in the flow. The results of this study indicate there is an unoptimal distribution channel for agricultural products, and the warehouse receipt system is the right alternative, and can be applied as one of the new distribution channels to overcome the drop of selling price during the harvest.